ISLAMIC ECONOMIC PERSPECTIVE ON INCLUSIVE ECONOMIC GROWTH IN INDONESIA: A VECM ANALYSIS OF CIGARETTE CONSUMPTION, LABOR FORCE PARTICIPATION, AND POPULATION GROWTH - Aulia Istiqomah; Moh. Bahrudin; Alief Rakhman Setyanto (Program Studi Ekonomi Syariah, Universitas Pangeran Diponegoro Nganjuk, 2026)
This study aims to analyze the effect of cigarette consumption, labor force participation rate (TPAK), and population growth on inclusive economic growth in Indonesia in the period 2005-2024, and interpret the results through the perspective of Islamic economics. The method used in this study is a quantitative approach with the type of explanatory study that applies the Vector Error Correction Model (VECM) to detect the dynamics of long-term relationships and short-term adjustments between variables. Research findings indicate that inclusive economic growth in Indonesia still faces serious challenges due to the high consumption of cigarettes that divert household funds allocation from productive needs as well as the need to improve the quality of TPAK and Population Growth Management in order to make a maximum contribution to the equitable distribution of welfare in accordance with the principles of benefit in Islamic economics.